Characterization of two new high-grade B-cell lymphoma cell lines with MYC and BCL2 rearrangements that are suitable for in vitro drug sensitivity studies. Issue 4 (21st March 2019) - Dheur, Marie-Sophie; Poirel, Hélène A.; Ameye, Geneviève; Tilman, Gaëlle; Saussoy, Pascale; Defour, Jean-Philippe; Camboni, Alessandra; Van Den Neste, Eric; Coulie, Pierre G.; van Baren, Nicolas
Abstract: High-grade B-cell lymphomas with MYC and BCL2 or BCL6 rearrangements are highly aggressive B-cell lymphomas called double-hit lymphomas (HGBL-DH). They are particularly refractory to standard treatments and carry a poor prognosis. Fragments of resected tumoral lymph nodes from two HGBL-DH patients were put in culture. Continuously proliferating cells were characterized and compared with the original tumors. In both cases, the proliferating cells and the tumor displayed MYC and BCL2 rearrangements. Both cell lines (called LB5848-LYMP and LB5871-LYMP) presented a high proliferation rate and were maintained in culture for more than one year. Upon injection in immunodeficient mice, LB5848-LYMP gave rise to lymphoid tumors. In vitro treatment of these cell lines with a BCL2-inhibitory drug (ABT-199) selectively stopped their proliferation. These new cell lines represent valuable tools for studying HGBL-DH and for the in vitro testing of candidate therapies targeting HGBL-DH. LB5848-LYMP is also suitable for similar experiments in vivo .